Interpretasi Perceraian dan Pernikahan Kembali dalam Matius 5:32 - Rick Gamelia; Arif Wicaksono; Marthin Steven Lumingkewas (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
Divorce and remarriage are common things in today's post-modern society. Both of these practices are also commonly found in the lives of Christians. This is due to a lack of proper understanding of the Christian view of divorce and remarriage to those who have been divorced. In order to understand this, the author tries to build an understanding of Christian teachings through the text of Matthew 5:32. The method used to reveal the essence of true teaching is a grammatical-contextual exegesis approach. The grammatical-contextual method pays attention to the original grammatical rules and the context of the text to be studied. The results show that Jesus taught that both divorce and marriage to a divorced person are serious matters. Divorce as a result of adultery or marriage to someone who has been divorced is mentioned as sexual immorality in Matthew 5:32. This behavior causes a person to place the burden of sin on divorced husbands, divorced wives and even husbands who take divorced wives to bear the same sin of adultery and live in adultery.